2008
DOI: 10.1371/journal.pgen.0040037
|View full text |Cite
|
Sign up to set email alerts
|

Offspring's Leukocyte Telomere Length, Paternal Age, and Telomere Elongation in Sperm

Abstract: Leukocyte telomere length (LTL) is a complex genetic trait. It shortens with age and is associated with a host of aging-related disorders. Recent studies have observed that offspring of older fathers have longer LTLs. We explored the relation between paternal age and offspring's LTLs in 4 different cohorts. Moreover, we examined the potential cause of the paternal age on offspring's LTL by delineating telomere parameters in sperm donors. We measured LTL by Southern blots in Caucasian men and women (n=3365), ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
264
4
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 242 publications
(288 citation statements)
references
References 55 publications
16
264
4
4
Order By: Relevance
“…Recently, a paternal inheritance model has been gaining favor. 8,[24][25][26] The most recent study suggesting paternal inheritance from Nordfjall et al 26 contained a total of 217 parent-offspring pairs. In our study we included a total of 1244 father-offspring pairs and 1388 mother-offspring pairs and found both significant mother-offspring and father-offspring correlations for TL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a paternal inheritance model has been gaining favor. 8,[24][25][26] The most recent study suggesting paternal inheritance from Nordfjall et al 26 contained a total of 217 parent-offspring pairs. In our study we included a total of 1244 father-offspring pairs and 1388 mother-offspring pairs and found both significant mother-offspring and father-offspring correlations for TL.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we found significant evidence for a positive association of paternal age with TL, supporting earlier reports. 24,27,28 At first glance, any positive association of TL with age seems counterintuitive. However, TL is known to be maintained, and even lengthened, in sperm, despite both mitotic and meiotic divisions during the proliferation and differentiation of the cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leukocyte telomere length is a biological marker of aging, and the telomere length of leukocytes of children of older fathers is higher than that of children of younger fathers. [86,[137][138][139]. However, the exact mechanism of longer offspring's leukocyte telomere length depending on paternal aging is not clear.…”
Section: Telomeresmentioning
confidence: 99%
“…However, the exact mechanism of longer offspring's leukocyte telomere length depending on paternal aging is not clear. Previous studies have suggested two mechanisms to explain the longer telomere length in spermatozoa of older men [86,139] (Table 4). The former explanation is high expression of testicular telomerase leading to extension of Salas-Huetos et al [118] telomeres of spermatozoa chromosomal ends with advanced age [140].…”
Section: Telomeresmentioning
confidence: 99%